Pengaruh Pemakaian Masker Bedah dan Masker Kain pada Wajah - Sutanto, Hans; Saroso, Ade; Setyaningrum, Dyah; Ilona, Florinda (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2022)
Background. Face masks are indispensable in preventing the spread of COVID-19 transmission. Face mask use can have beneficial and detrimental effects on a person. In this study, participants' faces were observed before and after wearing surgical and cloth masks for 4 hours per day for five consecutive days. Methods. The research design is experimental. Results. Thirty-two Trisakti University Faculty of Medicine employees aged 26 to 46 years and 18 men and 14 women, participated in this study. Sociodemographic data and facial examination were assessed at the start and end of the study. The research data obtained the results of p = 0.392. Conclusion. There is no significant difference between surgical and cloth masks in terms of acne, skin irritation, and redness.